Konsumsi BETN, SK, dan Lemak Kasar Kambing Kacang Jantan yang Mengalami Tingkat Pembatasan Pakan yang Berbeda - Seuk, Serlinda Seuk; Nahak, Oktovianus R.; Klau Tahuk, Paulus (Bantara Journal of Animal Science, 2023)
This study aims to determine the consumption of  nitrogen free extract (NFE), crude fiber (CF) and extract eter (EE) of male kacang goats in the feed restriction phase after experiencing different levels of feed restriction. The study used an experimental method with a completely randomized design (CRD) which consisted of 3 treatments and 5 replications, namely: T0: Cattle without food restrictions, T1: Cattle were limited to 100% feed according to maintenance life and T2: Cattle were limited to 50% of maintenance life. The results showed that the consumption NFE of natural grass of treatment T0 and T1 was relatively the same, but higher than T2 (P<0.05); conversely the consumption of NFE of concentrate was relatively the same (P>0.05) among the treatments; while the total consumption of NFE of natural grass and concentrate treatment T1 and T2 was relatively the same (P>0.05) and lower (P<0.05) than treatment T0. Consumption CF of natural grass in the T0 and T1 treatments was relatively the same (P>0.05) and higher (P<0.05) than the T2 treatment; On the other hand, the total consumption CF of natural grass and concentrates in the T1 and T2 treatments was relatively the same (P>0.05) and lower (P<0.05) than the T0 treatment. Likewise, the consumption EE of natural grass in the treatment of T0 and T1 was relatively the same (P>0.05) and higher (P<0.05) than treatment T2. The consumption of NFE and CF concentrates from the three treatments was relatively the same (P>0.05); Likewise, the consumption EE of concentrate and total consumption EE of natural grass and concentrate from male kacang goats in the feed restriction phase of the 3 different groups was not significant (P>0.05). Consumption of NFE for each treatment was T0 of 131.66 ± 41.42, T1 of 84.85 ± 38.88 and T2 of 83.70 ± 0.03. Consumption of crude fiber (g/head/day) for each treatment was T0 of 42.89 ± 6.33, T1 of 33.73 ± 9.52 and T2 of 26.96 ± 0.03. Consumption of extract eter (g/head/day) for each treatment was T0 of 5.52 ± 2.24, T1 of 3.23 ± 1.85, and T2 of 3.53 ± 0.00. It can be concluded that the restriction of feed (feed restriction) up to 50% of the maintenance life does hinder the livestock growth process, but does not interfere with the health status of goats (indicated and physiological status are in the normal range).